Modeling of 132 kV substation for insulation coordination - Mohammed Ariff, Mohd Hatta (2010)
Substation is an essential part of the grid systems which often regarded as the most expensive component in the power systems. In general, insulation coordination studies are an important and are used to determine the reliability of the substation. In most blueprints, the default design of a substation always being designed to have an absolute protections where all the possible stresses had already put into account according to the applied standard which sometimes being overprotected and expensive. The intention of this work is to model an existing substation in the way to investigate its design capability to withstand the excessive transient over voltage (i.e. lightning surge), in an attempt to have a more cost effective design model. The selected substation model is adopted from a 132 kV Simpang Renggam-Ayer Hitam substation. The substation is modeled using PSCAD/EMTDC software and the substation drawing details has been courteousness provided by the Tenaga Nasional Berhad (TNB). Throughout the model, several issues have been addressed and carried out in this study regarding the optimization of the substation design. Issues such as arrester placement strategies, determination of transformer breakdown current, arrester placement distance, as well as the energy handling capability for the arrester have been investigated. The findings unveil that; proper placement of arrester is crucially needed in order to optimize the substation performance in term of its reliability and cost effective. Besides that, the determination of current level associated to the breakdown of the transformer, could help the engineers to estimate the capability of the protection scheme in a way to improve the design. Moreover, the development of energy within the arrester which could cause the reduction of protection scheme potential is not only due to the magnitude of the stress current, but also influenced by other factors such as stress waveform durations and the geographical location of the substation. Finally, the highlight of this work is basically through the development of the substation model via PSCAD. It has become an alternative option for researchers to conduct various investigations in subject to substation design improvement and insulation coordination studies.